2023
DOI: 10.3897/neobiota.81.90473
|View full text |Cite
|
Sign up to set email alerts
|

Rarely naturalized, but widespread and even invasive: the paradox of a popular pet terrapin expansion in Eurasia

Abstract: The North American terrapin, the red-eared slider, has globally recognized invasive status. We built a new extensive database using our own original and literature data on the ecology of this reptile, representing information on 1477 water bodies throughout Eurasia over the last 50 years. The analysis reveals regions of earliest introductions and long-term spatio-temporal dynamics of the expansion covering now 68 Eurasian countries, including eight countries reported here for the first time. We established als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Indeed, Breuil [16] suggested that Trachemys species do not reproduce on mainland Guadeloupe. However, local climatic conditions in Guadeloupe fit particularly well with those associated with reproduction records of invasive populations of T. scripta [74]. In addition, observations of Trachemys in full courtship in the urban area of Les Abymes (Grande-Terre; see Video S1, Supplementary Materials) and regular observations of various ontogenic stages, including juveniles, are strongly suggestive that the Guadeloupe populations are reproducing.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, Breuil [16] suggested that Trachemys species do not reproduce on mainland Guadeloupe. However, local climatic conditions in Guadeloupe fit particularly well with those associated with reproduction records of invasive populations of T. scripta [74]. In addition, observations of Trachemys in full courtship in the urban area of Les Abymes (Grande-Terre; see Video S1, Supplementary Materials) and regular observations of various ontogenic stages, including juveniles, are strongly suggestive that the Guadeloupe populations are reproducing.…”
Section: Discussionsupporting
confidence: 63%
“…Third, both Trachemys species, and possibly P. castaneus, might be well adapted today to the local environment in Guadeloupe and be self-sustainable without additional introductions. The wide alien distribution of freshwater turtles may not necessarily imply the establishment of reproducing populations but may in some areas be explained by the recruitment of new individuals through regular additional releases [74]. Indeed, Breuil [16] suggested that Trachemys species do not reproduce on mainland Guadeloupe.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reproductive output of T. s. elegans (as measured by RCM per clutch) is more than twice that of T. s. scripta (see also Moll and Moll 1990), despite apparently similar nesting season lengths (Ernst and Lovich 2009:459) and annual clutch frequencies (Table 3), and much greater known longevity (47 yrs in T. s. elegans , Ernst and Lovich 2009; 25 yrs in T. s. scripta Gibbons 1987). The reason that T. s. elegans evolved such high reproductive output over a longer life compared with T. s. scripta is not yet clear, but no doubt contributes to its success as an invasive taxon around the world (Lowe et al 2000; Reshetnikov et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Trachemys scripta is one of the most prolific turtles in North America, producing up to 30 eggs/clutch and depositing up to 5 clutches/yr (Ernst and Lovich 2009), contributing to its success as one of the most invasive species on the planet (Lowe et al 2000;Reshetnikov et al 2023). The species has wide distribution and abundance; therefore, data on reproductive output are available for .40 populations within the native range (Table 1), although very few data are available from the southwestern part of the species' range (particularly in and near Arkansas).…”
mentioning
confidence: 99%